(untitled) (Temporalis, 2026)
This article seeks to confront the critique regarding the supposed impossibility of analyzing sexual diversity from a Marxist perspective in Social Work. To this end, it analyzes the incorporation of this debate into the profession; presents the ontological foundations for understanding sexual diversity; and discusses the current historical challenges for its articulation with Marxism, as well as the particularities related to sexual diversity.